Ruling Capital Emerging Markets and the Reregulation of Cross-Border Finance - Gallagher, Kevin P. (Cornell Studies in Money, 2014)
In Ruling Capital, Kevin P. Gallagher demonstrates how several emerging market and developing countries (EMDs) managed to reregulate cross-border financial flows in the wake of the global financial crisis, despite the political and economic difficulty of doing so at the national level. Gallagher also shows that some EMDs, particularly the BRICS coalition, were able to maintain or expand their sovereignty to regulate cross-border finance under global economic governance institutions. Gallagher combines econometric analysis with in-depth interviews with officials and interest groups in select emerging markets and policymakers at the International Monetary Fund, the World Trade Organization, and the G-20 to explain key characteristics of the global economy.